POLICY CONSIDERATIONS FOR THE UTILIZATION AND RATIONALIZATION OF PPE IN MATERNAL CARE DURING COVID-19 PANDEMIC – LITERATURE REVIEW - Soebangil, Mas Aditya; Gani, Ascobat; Oktamianti, Puput (UI Scholars Hub, 2023)
Policies regarding utilizing and rationalizing Personal Protective Equipment (PPE) during the COVID-19 pandemic challenge every healthcare service provider. Within the maternal health sector, it is suspected that the negative perception of patients and the lack of implementation and compliance with infection prevention and control policies disrupt the quality of care provided. This research is a narrative review highlighting all proper considerations for using and rationalizing PPE within the maternal health sector. Articles are gathered and filtered from well-known scientific publishing sites, and ten articles became the main discussion of this research. The utilization of PPE impacts all levels of maternal health service, from prenatal care to postnatal and neonatal care. Standardized PPE utilization and rationalization are needed to maintain the quality of care and reduce any negative impacts that PPE use might bring. Policies regarding the use of PPE must be well thought out to ensure that it will benefit its user without the risks of its side effects.